Functional Assessment in the Elderly and Patient Outcomes - Martins, Yolanda; Simões, Rita; Miranda, Marisa; Tavares, Luís Pedro (Portuguese Journal Internal Medicine, 2016)
Introduction: An easy-to-use new functional assessment tool named “AVD-DezIs” was created to perform geriatric assessment in Internal Medicine Department (IMD) in patients. This study aims to cross data on functional assessment in the elderly with patient outcomes. Material and methods: Functional assessment was performed with AVD-DezIs index. It consist in 4 items on basic daily living activities, 5 on instrumental activities and 11 on social and functional profile - maximum score is 20. This prospective study included all patients with 65 years or older admitted in IMD between September 2013 and October 2014, and aimed to cross data on functional assessment with length of stay, in hospital and after discharge mortality and readmissions. Statistical analysis was made with SPSS 20.0. Results: Aging contributes to increase the score AVD-DezIs (10.8-5.45), but not for the length of stay (9.8-12.2), in patients over 85 years old and under 75 years, respectively. There were no significant differences with regard to in-hospital mortality (82.3-79.9) and 30 days after discharge (80.9-80.2), readmissions in Emergency (80.3-80.2) and in IMD (80.3-79.6). There were no significant differences between the AVD-DezIs score and length of stay. In contrast, AVD-DezIs score was higher in patient who died during hospitalization (11.5-8.4) and in those who died until 30 days after discharge (12.2-8.4). Patients readmitted in IMD and Emergency had higher AVD-DezIs score than patients without readmission (9.7-8.1 e 10.2-8.4, respectively). Conclusion: Aging has no relation with higher length of stay, mortality and readmission. Instead, AVD-DezIs functional assessment is a good tool to predict these outcomes.